Doctoral education in Technology-Enhanced Learning: the perspective of PhD candidates and researchers - Athanasiou, Androulla; Nicolaou, Anna; Soule, Maria Victoria; Kakoulli-Constantinou, Elis; Parmaxi, Antigoni; Fominykh, Mikhail; Perifanou, Maria A.; Economides, Anastasios A.; Pedro, Luis; Albó, Laia; Hernández-Leo, Davinia; Wild, Fridolin (My University, 2023)
The ongoing and rapid development in technologies in the last few decades has given rise to a great amount of research in the area of Technology Enhanced Learning (TEL). O’Donnell and O’Donnell (2015) state that TEL supports teaching and learning through the use of technology and can carry a similar meaning to e-learning. However, Fominykh and Prasolova-Førland (2019, p. 38) add to this definition by indicating that TEL is not limited to the use of technologies for teaching purposes, being “a research field that explores new ways of learning enabled by technology and designing new technologies that can support learning in new ways.” The term TEL has also been coined as Educational Technology, Digital Education, and Learning Engineering, with the last term implying that this area requires technical competence in order to become involved in learning and development initiatives especially in areas that methodologically depend on data science, Computer Science and Learning Sciences (Pammer-Schindler et al., 2020). However, according to the authors, all terms “recognize the need of epistemic fluency to facilitate interdisciplinary dynamics” (ibid., p. 3), highlighting how the specific field overlaps with a variety of disciplines. This interdisciplinary aspect can become an indicator of the vast amount of research that has been conducted and will be in the future. However, as the knowledge and amount of data and published work in the specific field grows, the requirements with regards to researching TEL become more demanding. Research conducted on the use of technologies to support doctoral students’ learning proves that the affordances of technologies can be beneficial for doctoral students (Boulton, 2019); this applies especially where co-construction of knowledge is a course expectation and in cases where transnational doctoral students wish to share experiences. The appropriate choice of technologies can lead to a richer learning environment, inclusivity, intercultural communication and more engagement. Thus, training and guidance in conducting research and using technologies for learning at a Doctoral level may be a key activity in dealing with the ever-growing requirements in research. In particular, Chen (2012, p. 1) has identified that “due to a lack of formal research training and experience, students can find completing research projects a daunting task. This, coupled with a fear of statistics, can culminate in quite an overwhelming experience for many students”; while Dermo (2009) stated that the key aspect would be to improve the quality of students’ learning experience in higher education. Similarly, Pammer-Schindler et al. (2020), based on the results of the Doctoral Education for Technology-Enhanced Learning (DE-TEL) project, have also identified the need for providing doctoral training in TEL related areas. In particular, the DE-TEL project aimed to improve and innovate the European doctoral education in TEL, by identifying good practices in doctoral education in TEL and developing a new program for doctoral education in TEL and OERs The proposed paper aims at presenting part of the quantitative and qualitative results yielded from an online survey which aimed at collecting information on doctoral education in TEL from PhD candidates and researchers involved in doctoral education or carrying out research in TEL. The survey was designed based on prior secondary research (Pammer-Schindler et al., 2020). The questions of the survey were structured into eight thematic areas: professional background, TEL topics, general PhD education, research methods, learning sources, challenges, supervision and mentorship, and personal background. In the TEL topics, general PhD education and research methods groups, the respondents evaluated the importance and availability of educational resources on the corresponding topics. In this paper, we focus on the results of the two groups of questions: general PhD training topics and research methods. A total of 229 participants from 40 different countries around the globe responded to the survey. In terms of their educational background, 45% (n=103) were PhD candidates, 40.2% (n=92) held a PhD and 11.4% (n=26) a Master’s degree or equivalent, and this is their highest degree. Only 3.5% (n=8) of participants held a degree that is lower than a Master's degree or equivalent. In this study we report on the results of the first two groups. A mixed methods design was employed to analyse the data. Descriptive and inferential statistics were performed using SPSS to analyse the results of the closed-ended questions. Qualitative data analysis was used to analyse the results of the open-ended questions. Findings on the need of courses and educational materials on the general PhD training topics show that both PhD candidates and PhD holders agree on the need for “academic writing” courses as the most relevant course. However, both groups discern in their rank order of preferences for other courses. With regards to research methods, responses indicated that Design-based research is the most common method for both PhD students and Phd holders. An exception are researchers working in the field of ‘Education using technologies’, where experimental research and field qualitative methods are the most reported methods. Regardless of the level of training, the participants reported a need for more training in the research methods they work with. In terms of the learning sources used by the participants, the latter indicated that these were influenced by their educational background, although all tended to choose the academic publications as their primary learning source for TEL topics. For the general PhD-level training topics both PhD candidates and PhD holders selected the supervisor help as their primary learning source. Additionally, the data has also shown that three learning sources seem to be the most used by PhD candidates and PhD holders with regards to research methods: Supervisor help, Academic publications, and courses in the PhD program. The inferential results of the study showed statistically significant differences when it comes to the stage of PhD of students on the availability of courses and learning materials used. Specifically, as PhD students progress to the middle and late stages of their studies, they seem to have access to a wider range of resources and materials in topics related to academic writing (e.g. academic language style, supporting arguments with references, formats of academic journals and conferences) and dissemination of research results (e.g. submitting manuscripts to academic journals, research databases, open data, open science, social media, and reproducibility consideration). All in all, despite the increase in the availability of resources and materials as PhD students move to more advanced stages of their studies, the survey indicated that doctoral students need adequate support and training in academic writing and research methodologies. This has prompted the design and implementation of a training program for doctoral students by the DE-TEL consortium.
Keywords: Technology Enhanced Learning; Doctoral education